How to read literature - Eagleton, Terry 1943- (New Haven Yale University Press, 2013)
"What makes a work of literature good or bad? How freely can the reader interpret it? Could a nursery rhyme like Baa Baa Black Sheep be full of concealed loathing, resentment and aggression?In this accessible and delightfully entertaining book, Terry Eagleton addresses these intriguing questions and a host of others. How to Read Literature is the book of choice for students new to the study of literature and for all other readers interested in deepening their understanding and enriching their reading experience. In a series of brilliant analyses, Eagleton shows how to read with due attention to tone, rhythm, texture, syntax, allusion, ambiguity and other formal aspects of literary works. He also examines broader questions of character, plot, narrative, the creative imagination, the meaning of fictionality, and the tension between what works of literature say and what they show. Unfailingly authoritative and cheerfully opinionated, the author provides useful commentaries on Classicism, Romanticism, Modernism and Postmodernism alongside spellbinding insights into a huge range of authors, from Shakespeare and Jane Austen to Samuel Beckett and J. K. Rowling."--Inside dust jacket.
Openings -- Character -- Narrative -- Interpretation -- Value.
Includes index.
Keywords: Literature -- Philosophy; Authors and readers; Reader-response criticism; Literature -- Explication